Household Food Insecurity and Its Association with Behavioral Problems in Children Living in Urban Slums: Findings from Karachi, Pakistan (P04-081-19) - Shah, Nadia (Curr Dev Nutr, 2019)
OBJECTIVES: 1. To determine prevalence of Household Food Insecurity in urban slums of Karachi. 2. To assess children's behavior living in a state of food insecurity in urban slums. 3. To relate Household food insecurity with child's behavior. METHODS: The study used a cross-sectional descriptive survey; conducted in 12 towns from all six districts of Karachi using multi-stage sampling methods. The structured questionnaire, comprised of Socio-demographic information, Household Food Insecurity Access Scale (HFIAS) and Child's behaviour questionnaire (CBQ) was conducted among 400 mothers of children bearing age 3 to 11 years living in urban slums. Correlation of HFIAS and CBQ scores were measured by Spearman's correlation coefficient. Generalized linear regression analysis was performed to determine relationship between scores of food insecurity and child behavior. RESULTS: Every two out of three households were found food insecure. 70% of households were worried for shortage of food in past month. Almost all households endured insufficient quality (95%) while 84.2% households did not have sufficient quantity of food in past month. Overall 70% mothers reported behavioral problems in their children; of which solitary and aggressiveness were the most common behavioral problems. Subsequent misbehavior reported were: avoiding going to school, stressed, impetuous, fearful, somatic complaints, bullied and not confident. Correlation between food insecurity and child misbehavior was significantly positive. One additional household with food insecurity increased 26.7% behavioral problems in children in urban slums. CONCLUSIONS: Food insecurity in slum areas of Karachi is rampant. Behavioral problems in children living in areas with food insecurity are at subsequent high risk. Strategies must be derived for related interventions to reduce these psycho-social problems in addition to socioeconomic problems. FUNDING SOURCES: No funding was available for the research. Authors conduction self research.